2019
DOI: 10.3389/fmicb.2019.02223
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting the Function of the C-Terminal Extension of the Escherichia coli [NiFe]-Hydrogenase 2 Large Subunit Precursor

Abstract: The active site of all [NiFe]-hydrogenases (Hyd) has a bimetallic NiFe(CN)2CO cofactor that requires the combined action of several maturation proteins for its biosynthesis and insertion into the precursor form of the large subunit of the enzyme. Cofactor insertion is an intricately controlled process, and the large subunit of almost all Hyd enzymes has a C-terminal oligopeptide extension that is endoproteolytically removed as the final maturation step. This extension might serve either as one of the recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This conclusion is in contrast to in vitro experiments showing the interaction of the apo‐form of the large subunit of E. coli Hyd‐2 with the Hyp protein delivering the Fe(CN) 2 (CO) unit of the active site was abolished in the absence of the C‐terminal extension (Senger et al, 2017). However, there are strong indications that rather the N‐terminus of the large subunit is involved in the interaction with the Hyp machinery (Albareda, Buchanan, & Sargent, 2017; Kwon et al, 2018; Pinske, Thomas, Nutschan, & Sawers, 2019; Thomas et al, 2015). Just recently, the crystal structure of apo‐HyhL, the large subunit of the [NiFe]‐hydrogenase from T. kodakarensis , in complex with the nickel‐inserting maturase HypA has been resolved (Kwon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is in contrast to in vitro experiments showing the interaction of the apo‐form of the large subunit of E. coli Hyd‐2 with the Hyp protein delivering the Fe(CN) 2 (CO) unit of the active site was abolished in the absence of the C‐terminal extension (Senger et al, 2017). However, there are strong indications that rather the N‐terminus of the large subunit is involved in the interaction with the Hyp machinery (Albareda, Buchanan, & Sargent, 2017; Kwon et al, 2018; Pinske, Thomas, Nutschan, & Sawers, 2019; Thomas et al, 2015). Just recently, the crystal structure of apo‐HyhL, the large subunit of the [NiFe]‐hydrogenase from T. kodakarensis , in complex with the nickel‐inserting maturase HypA has been resolved (Kwon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a major role of the C‐terminal extension might be providing indirectly the N‐terminus with sufficient flexibility to interact with the Hyp machinery. A role of the C‐terminal extension in enhancing structural flexibility to facilitate the interaction with Hyp proteins has also been proposed (Albareda, Pacios, & Palacios, 2019; Pinske et al, 2019). A function as a maturation facilitator would also explain why the removal of the C‐terminal extension does not necessarily lead to immature hydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent experiments conducted to unravel the chaperone function of the C-terminal extension of the Escherichia coli [NiFe]hydrogenase 2 large subunit precursor support this assumption. 7 In the present study, we focused our attention on the large subunit of the regulatory hydrogenase (RH) from R. eutropha, which belongs to the small subgroup of [NiFe]-hydrogenases whose large subunits do not possess a C-terminal extension. 8 The RH contains an otherwise standard-like catalytic center (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Early work showed that swapping of the E. coli HycE (Hyd-3) assembly peptide for that of HybC (Hyd-2) led to a ‘dead-end’ fusion protein that could not be processed by any maturation protease tested [ 43 ]. While more recently, swapping the HybC (Hyd-2) assembly peptide for that of HyaB (Hyd-1) did not lead to any changes in the requirement for the Hyd-2-specific protease (HybC) for maturation [ 42, 44 ].…”
Section: Full-textmentioning
confidence: 99%
“…It is becoming increasingly clear that the C-terminal assembly peptide may not be the key recognition motif for the protease [34,42]. Early work showed that swapping of the E. coli HycE (Hyd-3) assembly peptide for that of HybC (Hyd-2) led to a 'dead-end' fusion protein that could not be processed by any maturation protease tested [43].…”
mentioning
confidence: 99%